Evaluation of the Families, Attitudes toward Environment Pollution - qassim, Wissam; abed, rajaa (Iraqi National Journal of Nursing Specialties, 2014)
Objectives: To evaluate the families’ attitudes toward environment pollution, and determine the relationship between families’ attitudes towards environment pollution and their demographic characteristics of age, education, type of family, and socioeconomic status. Methodology: A descriptive design is carried throughout the present study to evaluate families’ attitudes toward environment pollution for the period of October 5th2013 to May 7th2014. A non-probability "purposive" sample of (110) families’ is selected. The sample is comprised of two groups; (75) urban families’ and (35) rural ones. An evaluation tool is designed and constructed for the purpose of the study. It is consisted of (4) main parts; demographic data, attitudes toward environment pollution, attitudes toward producing factors for house environment pollution, and method of house environment arrangement. Content validity and internal consistency reliability are determined for the study instrument through a pilot study. Data are collected through the use of the study instrument and structured interview as means of data collection. Data are analyzed through the application of descriptive data analysis approach, which includes frequency, percent and mean of scores. Results: The results of the study indicate that the vast majority of families’ has experienced high level of attitudes toward environment pollution, producing factors for house environment pollution, and method of house environment arrangement. Recommendations: The study recommends that education program by mass media can be forwarded to families’ with regard to issues related to environment pollution in order to increase their awareness, improves their attitudes, and positively change their behaviors